MANAGERIAL PERFORMANCE ANALYSIS: BUDGET EVALUATION THROUGH MOTIVATION IN THE MERANGIN DISTRICT GOVERNMENT - Saukani, Saukani; Yunus, Mukhlis; Elfisa, Yesi; Usvita, Mega (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTThe role of managers is crucial to the success of an organization. With the role that is owned by the manager becomes the individual who is most responsible for the implementation of organizational activities within the framework of the goals that have been set. So, the success of an organization can be seen from its managerial performance. This study aims to determine the effect of evaluation on managerial performance with motivation as an intervening variable. This research is a survey research by distributing questionnaires to structural officials of SKPD Esselon II, Esselon III and Esselon IV at the Merangin District Government. Of the 191 questionnaires distributed, 122 were returned. There are 4 questionnaires that are not filled out completely, so there are 118 questionnaires that can be processed in this study. The analytical method used in this research is Variant-based SEM using SmartPLS Software. From the results of testing the proposed hypothesis, it shows that motivation is not able to act as a mediation in the evaluation of managerial performance evaluation.Keywords:Managerial Performance, Budget Evaluation, Motivation